Complexes Containing a Phenol–Platinum(II) Hydrogen Bond: Synthons for Supramolecular Self‐Assembly and Precursors for Hydridoplatinum(IV) Complexes. Issue 24 (12th June 2019) - Behnia, Ava; Fard, Mahmood Azizpoor; Boyle, Paul D.; Puddephatt, Richard J.
Abstract : The cycloneophylplatinum(II) complexes [Pt(CH2 CMe2 C6 H4 )(κ 2 ‐NN′‐2‐C5 H4 NCH2 ‐NH‐R], R = 2‐C6 H4 OH, 1 ; R = 3‐C6 H4 OH, 2 ; R = 4‐C6 H4 OH, 3, and [Pt(CH2 CMe2 C6 H4 )(κ 2 ‐NN′‐2‐C5 H4 NCH=N‐2‐C6 H4 OH)], 4, are reported. The structures of 1 and 4 each contain an intramolecular OH·· Pt hydrogen bond, while complex 3 contains an intermolecular OH·· Pt hydrogen bond and forms a new type of supramolecular polymer. In contrast, the complex [PtCl2 (κ 2 ‐NN′‐2‐C5 H4 NCH=N‐2‐C6 H4 OH)], 5, forms a dimer through intermolecular OH·· ClPt hydrogen bonding. Reaction of complex 4 with HCl or HBr occurs by oxidative addition to give hydridoplatinum(IV) complexes [PtHX(CH2 CMe2 C6 H4 )(κ 2 ‐NN′‐2‐C5 H4 NCH=N‐2‐C6 H4 OH)], 6, X = Cl; 7, X = Br. The sequential formation of isomers of these compounds is interpreted in terms of a proposed reaction mechanism. Abstract : Electron‐rich organoplatinum complexes can form intramolecular or intermolecular OH·· Pt hydrogen bonds, but formation of hydroplatinum(IV) complexes requires a strong acid such as HCl.